2022
DOI: 10.3390/nu14204303
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the Prevention and Treatment of Gestational Diabetes Mellitus (GDM): A Review

Abstract: Gestational diabetes mellitus (GDM)is one of the most common perinatal pathologies, with a prevalence of 5–20% depending on the population or diagnostic standards. It is diagnosed when glucose intolerance is first detected during pregnancy. In the pathogenesis of GDM, genetic, environmental, and pregnancy-related factors (excessive fat storage and increased adipokine and cytokine secretion) play important roles. A growing amount of scientific data has indicated the role of gut microbiota (GM) dysbiosis in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Another experiment revealed that relative weights of mesenteric white adipose tissue (mWAT), epididymal white adipose tissue (eWAT), and renal white adipose tissue (kWAT) were increased in mice related with low relative abundance of Ralstonia . It was supposed that Ruminococcaceae had a close relationship with fat deposition ( Kaminska et al., 2022 ). In the previous discussion, it was noticed that the high body fat group's gut exhibited a higher abundance of Ruminococcaceae UCG-005 .…”
Section: Discussionmentioning
confidence: 99%
“…Another experiment revealed that relative weights of mesenteric white adipose tissue (mWAT), epididymal white adipose tissue (eWAT), and renal white adipose tissue (kWAT) were increased in mice related with low relative abundance of Ralstonia . It was supposed that Ruminococcaceae had a close relationship with fat deposition ( Kaminska et al., 2022 ). In the previous discussion, it was noticed that the high body fat group's gut exhibited a higher abundance of Ruminococcaceae UCG-005 .…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic supplements were suggested to improve glucose, insulin, and lipid metabolism and decrease inflammatory response, reducing the risk for GDM and unfavorable pregnancy outcomes [ 45 , 46 ]. The mechanisms by which probiotic supplements alter glucose metabolism include the production of short-chain fatty acids, which were found to (1) regulate the production of hormones such as leptin and grehlin [ 47 ], affecting energy intake and expenditure, (2) increase the intestinal expression of peptide YY and glucagon-like peptide-1 (GLP-1) hormones, which act to increase insulin sensitivity [ 48 ], and (3) enhance the production of glucagon-like peptide-2 (GLP-2), which reduces inflammation [ 49 , 50 ]. Probiotic administration in women with GDM was also reported to reduce inflammatory markers, such as high-sensitivity C-reactive protein, tumor necrosis factor-α, and interleukin-6 [ 14 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the abundance of some genera of bacteria is associated with glucose metabolism in GDM women [ 53 ] and gut microbiota could be mediating the increase in BMI of infants born to GDM women [ 54 ]. Interestingly, it is suggested that treatment with probiotics could improve insulin sensitivity, glycemic control, and pregnancy outcomes in GDM women [ 55 , 56 , 57 ]. In this line, treatment with polyphenols improves gut microbiota dysbiosis in both animal models and human studies, which is also related to the reduction of systemic inflammation that is common in GDM and PE [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%